Tinjauan Yuridis Akibat Hukum terhadap Keabsahaan Jual Beli di Bawah Tangan dengan Kuitansi Berdasarkan Putusan: Studi Putusan Nomor 217/Pdt. G/2022/PN. Pbr - Ganda Prasetya Butar Butar; hasim purba; suprayitno (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The practice of under-hand land sale and purchase using a receipt (kuitansi) as evidence remains common in Indonesian society, despite the normative requirement that the transfer of land rights must be conducted before a Land Deed Official (PPAT) pursuant to Government Regulation Number 24 of 1997 on Land Registration. This study employs a normative legal approach with a case study method, examining the validity of a receipt as proof of land sale and purchase and analyzing the judge's considerations in deciding the case based on Decision Number 217/Pdt.G/2022/PN.Pbr. The findings indicate that a land sale and purchase evidenced solely by a receipt may be declared legally valid provided it fulfills the requirements under Article 1320 of the Indonesian Civil Code and the principles of cash payment, publicity, and real transaction, as considered by the judge on the basis of the plaintiff's good faith.